Divide and Conquer: The Aggravation of Social Segregation by Gated Communities - Mohd Suhaimi, Asnida (2010)

(untitled)
Gated communities are gaining popularity amongst the urban populace, particularly in the Klang Valley and have been associated with a better level of security, a stronger sense of community and a richer social capital compared to conventional housing schemes. Despite the growing number of gated community housing schemes, the developments of gated communities have gone unchecked for several years by the relevant authorities. Several issues have emerged with regards to such developments, such as the legality of gated communities and the potential social implications of such scheme on society. This paper intends to examine the developments of gated communities in Malaysia and discuss the legal and social implications of gated communities based on the research and surveys carried out by the writer in two gated communities in the Klang Valley. It will also explore the policies undertaken by some local authorities in relation to the developments of gated communities and guarded communities, and the potential impact of such developments on the community and urban sustainability.